Developing a Love-Based Curriculum Model with Islamic Digitalization in Islamic Education Learning in the Society 5.0 Era - Aria Nur Farida Muslicha; Sri Endang Herudiati (Jurnal Studi Pendidikan Agama Islam, 2026)
This study aims to develop a love-based curriculum model integrated with Islamic digitalization to support Islamic education learning in the Society 5.0 era. The research employed a Research and Development (R&D) approach consisting of needs analysis, conceptual design, expert validation, limited implementation, revision, and final model formulation. The results of the needs analysis showed that Islamic education still faces challenges in balancing character formation with the rapid development of digital technology. Therefore, a curriculum model that integrates compassion-based pedagogy, Islamic ethical values, and responsible digital learning is required. The developed model emphasizes value-based objectives, humanistic learning strategies, Islamic digital media, and character-based assessment. Validation results indicated that the model is conceptually appropriate and applicable in Islamic education settings. Limited implementation demonstrated that the model improves students’ moral awareness, responsible digital behavior, and active participation in learning. The model also contributes to the goals of sustainable education by promoting quality learning, ethical digital literacy, and social responsibility. This study concludes that the integration of a love-based curriculum with Islamic digitalization can serve as an alternative framework for developing adaptive, humanistic, and value-oriented Islamic education in the Society 5.0 era.